Facile synthesis, stabilization, and anti-bacterial performance of discrete Ag nanoparticles using Medicago sativa seed exudates - Lukman, Audra I.; Gong, Bin; Marjo, Christopher E.; Roessner, Ute; Harris, Andrew T. (Journal of colloid and interface science, 2011)
Various colloidal Ag nanoparticles that were synthesized by M. sativa seed exudates in aqueous system under mild and non-photomediated conditions. [Display omitted] ► Medicago sativa seed exudate is effective at reducing Ag salts to form and stabilize Ag(0) nanoparticles ► The particle size and shape can be modulated by varying Ag concentration, quantity of exudate, and pH ► The Ag particles were spherical, flower-like and triangular in shape, ranging from 5 to 108 nm in size ► Unpurified Ag nanoparticles have the capacity to inhibit the growth of certain bacteria. The biogenic synthesis of metal nanomaterials offers an environmentally benign alternative to the traditional chemical synthesis routes. Colloidal silver (Ag) nanoparticles were synthesized by reacting aqueous AgNO 3 with Medicago sativa seed exudates under non-photomediated conditions. Upon contact, rapid reduction of Ag + ions was observed in <1 min with Ag nanoparticle formation reaching 90% completion in <50 min. Effect of Ag concentration, quantity of exudate and pH on the particle size and shape were investigated. At [Ag +] = 0.01 M and 30 °C, largely spherical nanoparticles with diameters in the range of 5–51 nm were generated, while flower-like particle clusters (mean size = 104 nm) were observed on treatment at higher Ag concentrations. Pre-dilution of the exudate induced the formation of single-crystalline Ag nanoplates, forming hexagonal particles and nanotriangles with edge lengths of 86–108 nm, while pH adjustment to 11 resulted in monodisperse Ag nanoparticles with an average size of 12 nm. Repeated centrifugation and redispersion enhanced the percentage of nanoplates from 10% to 75% in solution. The kinetics of nanoparticle formation were monitored using ultraviolet–visible spectroscopy and the Ag products were characterized using transmission electron microscopy, selected-area electron diffraction, scanning electron microscopy, X-ray powder diffraction, and atomic force microscopy. X-ray photoelectron spectroscopy was used to investigate the elements and chemical environment in the top layers of the as-synthesized Ag nanoparticles, while the metabolites in the exudate were analyzed using gas chromatography–mass spectroscopy. To our knowledge, this is the first account of M. sativa seed exudate assisted synthesis and stabilization of biogenic Ag nanoparticles; the nanoplates are notably smaller and better faceted compared with those synthesized by vascular plant extracts previously reported. Stabilized films of exudate synthesized Ag nanoparticles were effective anti-bacterial agents.